SISTEM INFORMASI ADMINISTRASI HRD BERBASIS WEB MENGGUNAKAN ADMINISTRATIVE WORKFLOW SYSTEM - Panca Rahardiyanto; Irma Azzahrah (SPIRIT, 2019)
The development of information technology and computers is growing faster, has indeed become one of the factors that contribute to the growth and development of a company as is the case with PT XYZ, a company engaged in the export import of processed seafood. The company has several different departments and functions according to their respective authorities. One of them is the Human Resources Development (HRD) section that is responsible for managing existing staffing data in the company environment and managing the administration of employee permits which currently use manual processes. Some problems occur including scattered letters, misdirected letters, handling letters that spend time, inefficient use of labor, handling of jobs that are not optimal, it is difficult to track the position of letters and status of letters not recorded properly and many more. To assist the company in solving existing problems, a web-based HRD administrative information system was created with the application of administrative workflow systems that are used as a means to automate HRD administrative processes such as process flow, approval and record keeping. All processes have been well integrated and produce programmed and timely reports. Keywords: information systems, Human Resources Development, administrative workflow system